Effects of Long-Term Dietary Administration of Kale ( Brassica oleracea L. var. acephala DC) Leaves on the Antioxidant Status and Blood Biochemical Markers in Rats - Katarzyna Papierska; Ewa Ignatowicz; Jadwiga Jodynis-Liebert; Małgorzata Kujawska; Róża Biegańska-Marecik (Polish Journal of Food and Nutrition Sciences)
Kale ( Brassica oleracea L. var. acephala DC) is a leafy green vegetable which belongs to the Brassicaceae family, one of the most commonly cultivated and consumed edible plants. The aim of this study was to investigate the potential adverse effects and antioxidant properties of freeze-dried kale leaves in 90-day dietary experiment on Wistar rats. The kale leaf powder was added to a diet at levels: 10, 30, and 60 g/kg feed. The standard blood biochemical and hematological markers, antioxidant enzyme activities, level of lipid peroxidation, reduced glutathione content, and damage to DNA in the liver were measured. Antioxidant potential in serum was measured and expressed as Trolox equivalents antioxidant capacity (TEAC). The kale leaf phytochemicals, i.e., glucosinolates, phenolic acids and flavonols, were quantified. Major glucosinolates were glucoiberin (164.6 mg/100 g d.w.) and glucobrassicin (130.6 mg/100 g d.w.), whereas kaempferol (159.1 mg/100 g d.w.), quercetin (119.6 mg/100 g d.w.), and sinapic acid (73.8 mg/100 g d.w.) dominated among phenolics. The lowest dose of kale leaves augmented the activity of catalase by 34% in males and by 44% in females. The highest applied dose increased activities of glutathione reductase by 31%, superoxide dismutase by 27%, and glutathione S-transferase by 24% in males only. Kale administration did not affect the activities of glutathione peroxidase and paraoxonase 1, glutathione concentration, lipid peroxidation level, and the level of DNA damage in the liver and the whole blood leukocytes. TEAC increased upon all doses of kale leaves by 30–90% in males and by 40–90% in females. The diet with kale did not affect blood biochemical and hematological markers. Results confirm no adverse effects of dried kale leaves used in model rat’s diet up to 60 g/kg for 90 days. The changes in hepatic antioxidant enzymes and plasma TEAC suggest beneficial effect of kale leaves on the antioxidant status in rats. Interestingly, these changes were more pronounced in male versus female animals.